2023
DOI: 10.1111/cobi.14081
|View full text |Cite
|
Sign up to set email alerts
|

How expert insight into alpine peatland conservation complements global scientific evidence

Abstract: Article impact statement: Experts' local experiences of management effectiveness, when collated and documented, align with and build on global scientific evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Establishing effective management to protect peatlands from burning and enhance recovery postfire will be vital to conserving these vulnerable ecosystems worldwide. Fewer questions focused on invasive species management, suggesting the past strong research focus on this threat has improved our understanding in Australia (Rowland et al, 2023). However, identifying range‐shifting species under climate change was a major concern for Australian experts, and has also been identified as an issue of global concern for mountain ecosystems (e.g., in Europe: Grzybowski & Glińska‐Lewczuk, 2020; Petitpierre et al, 2016).…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Establishing effective management to protect peatlands from burning and enhance recovery postfire will be vital to conserving these vulnerable ecosystems worldwide. Fewer questions focused on invasive species management, suggesting the past strong research focus on this threat has improved our understanding in Australia (Rowland et al, 2023). However, identifying range‐shifting species under climate change was a major concern for Australian experts, and has also been identified as an issue of global concern for mountain ecosystems (e.g., in Europe: Grzybowski & Glińska‐Lewczuk, 2020; Petitpierre et al, 2016).…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Clearly, the evidence required to check whether these assumptions are valid (i.e., that the Situation Analysis and Theory of Change are valid) should come from a range of sources including, but not limited to, Indigenous and Local Knowledge, experience, and wisdom of practitioners and partners, scientific studies and syntheses, expert well as fill knowledge gaps in the scientific literature (MacLeod et al, 2022;Rowland et al, 2023). There is therefore growing recognition that evidence that comes in a variety of types and subjects from local and external sources is required to make successful, pragmatic decisions in conservation under challenging time, resource, and cost constraints (Game et al, 2018;Malmer et al, 2020;Schuster et al, 2019;Sutherland et al, 2022;Taper et al, 2021;Tengö et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, local information from diverse sources can be highly relevant and reliable in specific conservation contexts, and considerations of local factors influence the effectiveness, costs, acceptability, and feasibility of actions (Adams & Sandbrook, 2013; Christie, Downey, et al, 2022). Meaningfully involving local communities and partners in conservation decisions has also been shown to add value to local projects and strategies, and ultimately underpin their success (Cote et al, 2021), as well as fill knowledge gaps in the scientific literature (MacLeod et al, 2022; Rowland et al, 2023). There is therefore growing recognition that evidence that comes in a variety of types and subjects from local and external sources is required to make successful, pragmatic decisions in conservation under challenging time, resource, and cost constraints (Game et al, 2018; Malmer et al, 2020; Schuster et al, 2019; Sutherland et al, 2022; Taper et al, 2021; Tengö et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Peatlands are waterlogged ecosystems that accumulate organic matter from partial plant decomposition (van Bellen & Larivière, 2020) and regulate water flow and quality (Shuttleworth et al, 2019). Wallowing by sambar deer has been identified as a threatening process for peatlands in south‐eastern Australia (Victoria's Flora and Fauna Guarantee Act 1988 ), and it has been suggested that culling would reduce these impacts (Parliament of Victoria, 2017; Rowland et al, 2023). Our management‐scale experiment used a BACI design to evaluate how ground‐based culling altered sambar deer impacts on peatlands.…”
Section: Introductionmentioning
confidence: 99%